The romance of the forest - Radcliffe, Ann, 1764-1823 (Oxford world's classics., 2020)
This novel is the epitome of the Gothic novel - a beautiful, orphaned heiress, a dashing hero, a dissolute, aristocratic villain and a ruined abbey deep in a great forest are combined by the author in a tale of suspense where danger lurks behind every secret trap-door.